Clinical and Diagnostic Characteristics of Rosai Dorfman Disease: A Case Series - Alrabiah, Khaled; Aractingi, Selim; Sohier, Pierre (International Journal of Innovative Research in Medical Science, 2022)
Rosai-Dorfman disease (RDD) is an exceedingly rare nonmalignant histiocytic condition of unknown etiology. Immunohistochemistry reveals that RDD cells are S-100 positive and CD1a negative. Emperipolesis is a frequent histological finding that is not exclusive to RDD. Although lymph node and cutaneous signs are the most common, other organs might be affected. Regardless of therapy, the clinical course is uncertain. We describe a series of nine instances with lymph node and/or cutaneous lesions. Lymph nodes were shown to be involved in a variety of locations, including the mediastinum and retroperitoneum. The therapeutic response to steroids was varied, and the response to chemotherapy was unsatisfactory. Two individuals had associated autoimmune illnesses (Sjögren syndrome and vasculitis). In a follow-up, these individuals had a positive outcome regardless of therapeutic mode.